Part 1)
(x²+15x+65)+(2x-5)*(3x+8)
(x²+15x+65)+(6x²+16x-15x-40)
(7x²+16x+25)
the answer Part 1) is the letter B
(7x²+16x+25)
Part 2)
(4x+1)*(3x-4)-(5x²-10x-12)
(4x+1)*(3x-4)-(5x²-10x-12)
(12x²-16x+3x-4)-(5x²-10x-12)
(7x²-3x+8)
the answer Part 2) is the letter D
(7x²-3x+8)
Part 3)
(8x²+19x+4)+(3x+2)*(x-5)
(8x²+19x+4)+(3x²-15x+2x-10)
(11x²+6x-6)
the answer part 3) is the letter A
(11x²+6x-6)
Part 4)
(6x+1)*(3x-7)-(7x²-34x-20)
(18x²-42x+3x-7)-(7x²-34x-20)
(11x²-5x+13)
the answer Part 4) is the letter C
(11x²-5x+13)
Find the axis of symmetry for this parabola.
y = 3x2 - 6x - 9
x = -3
☆☆☆☆☆☆☆☆☆☆☆☆☆☆☆x = 1
x = 3
x=4
-b/2a=-(-6)/2(3)
=6/6=1
Answer: always
Step-by-step explanation:
Hi Vanessa
3x -1/9 (27) =18
3x - 27/9 =18
3x- 3 =18
Add 3 to both sides
3x-3+3=18+3
3x=21
Divide both sides by 3
3x/3= 21/3
x= 7
The value of x is 7
Now let's check if my answer is correct
To check it we gonna replace x by 7 and 27 for y
(3)(7) -1/9 (27) = 18
21 -1/9 (27)=18
21- 27/9 = 18
21- 3 = 18
18 = 18
The answer is good and I hope its help:0